SPECIALIZATION PROCESS FOR THE BIOENGINEERING SECTOR IN THE MEDITERRANEAN ENVIRONMENT. ECOMED PART I. TRAINING MODULES - Sangalli, Paola (2020)
The promotion and greater adoption of soil bioengineering in the Mediterranean ecoregion is the main aim of the Erasmus + ECOMED project. This aim is being achieved by generating sector-specific theoretical and practical materials and tools essential for the specialization process and enhancement of this sector in the region of interest which is at the core of the ECOMED project strategy and approach. The lack of specialized training, a collection of analysed case studies and shortage of specialized staff in Mediterranean countries, makes it a necessity to develop training courses and a handbook on soil and water bioengineering implementation, along with hazard assessment methods and effective selection of methods specific to the Mediterranean environment.